2021
DOI: 10.1002/fsn3.2391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic administration with human thioredoxin‐1 transplastomic lettuce on diabetic mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Human metagenome-wide association studies in patients with type 2 diabetes demonstrated highly significant correlations between hyperglycemia and IR and specific intestinal bacteria, bacterial genes, and associated metabolic pathways [ 68 ]. Hyperglycemia affects goblet cell proliferation, maturation, and mucus biosynthesis, which will disrupt the intestinal barrier and intestinal mucus, allowing pathogenic bacteria and their elements, such as LPS, to pass through the epithelial barrier [ 69 , 70 ]. Subsequently, LPS binds to toll-like receptors on the surface of intestinal epithelial cells to recruit immune cells in the intestine [ 67 , 71 ].…”
Section: Gdm–gut Interactionmentioning
confidence: 99%
“…Human metagenome-wide association studies in patients with type 2 diabetes demonstrated highly significant correlations between hyperglycemia and IR and specific intestinal bacteria, bacterial genes, and associated metabolic pathways [ 68 ]. Hyperglycemia affects goblet cell proliferation, maturation, and mucus biosynthesis, which will disrupt the intestinal barrier and intestinal mucus, allowing pathogenic bacteria and their elements, such as LPS, to pass through the epithelial barrier [ 69 , 70 ]. Subsequently, LPS binds to toll-like receptors on the surface of intestinal epithelial cells to recruit immune cells in the intestine [ 67 , 71 ].…”
Section: Gdm–gut Interactionmentioning
confidence: 99%